2019
DOI: 10.21320/2500-2139-2019-12-2-145-153
|View full text |Cite
|
Sign up to set email alerts
|

Blinatumomab in the Treatment of Acute Lymphoblastic Leukemia: Russian Multicenter Clinical Trial

Abstract: Актуальность. Успехи в терапии рецидивов и рефрактерного острого лимфобластного лейкоза (Р/Р ОЛЛ) в последние годы связаны с внедрением методов иммунотерапии, в т. ч. биспецифического активатора собственных T-клеток пациента блинатумомаба (Блинцито™, Амджен ®) (БЦ). Цель. Оценить эффективность и токсичность БЦ в лечении пациентов с Р/Р ОЛЛ и с персистенцией минимального опухолевого клона до и после трансплантации аллогенных гемопоэтических стволовых клеток (аллоТГСК). Материалы и методы. В исследование включен… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Blinatumomab is a bispecifi c T-cell engager (BiTE) antibody designed to link T cells and CD19-positive B cells, which allows the patient's endogenous T cells to recognize and eliminate CD19-positive ALL blasts [8]. Blinotumomab is highly eff ective in R/R ALL patients with 69% of complete remission (CR), or with incomplete hematologic recovery achieved even aft er alloHSCT [4,[9][10]. Jabbour et al reported 68 patients with R/R B-cell ALL with blinatumomab failure, 38 (56%) of them was initially refractory to this treatment [11].…”
Section: Discussionmentioning
confidence: 99%
“…Blinatumomab is a bispecifi c T-cell engager (BiTE) antibody designed to link T cells and CD19-positive B cells, which allows the patient's endogenous T cells to recognize and eliminate CD19-positive ALL blasts [8]. Blinotumomab is highly eff ective in R/R ALL patients with 69% of complete remission (CR), or with incomplete hematologic recovery achieved even aft er alloHSCT [4,[9][10]. Jabbour et al reported 68 patients with R/R B-cell ALL with blinatumomab failure, 38 (56%) of them was initially refractory to this treatment [11].…”
Section: Discussionmentioning
confidence: 99%
“…Blinotumomab is highly effective in R/R ALL patients with 69% of complete remission or complete remission with incomplete hematologic recovery achieved even after allo-HSCT [7][8][9]. In TOWER study the 1-year, the overall survival (OS) rate was 36% (median OS, 7.7 months), and the duration of remission was 7.3 months.…”
Section: Discussionmentioning
confidence: 99%